التنظيم القانوني للممارسة الصحفية الالكترونية في الجزائر - عكه, زكريا (Université de M'sila, 2018)
يعرف الفضاء الإعلامي يوما بعد يوم تحولات جذرية متنامية ، وهذا بازدياد استخدام شبكات الانترنت وما تتيحه من تطبيقات و تسهيلات ، و أصبحت الصحافة الالكترونية جزء لا يتجزأ من المشهد الإعلامي سواء كان محليا ، وطنيا ، أو دوليا . خصوصيات تلك للصحافة جعلتها تتبوأ الصدارة إعلاميا و الفضل يعود بالدرجة الأولى الى ما تتيحه الشبكة العنكبوتية من آنية و سرعة في بث وتغطية وتداول المعلومة و الخبر. إلا أن هذا النوع الإعلامي الجديد طرح إشكالية تنظيمه وضبطه من الناحية القانونية ، و الجزائر من بين الدول التي تدخلت مؤخرا لتنظيم و تأطير هذه الوسيلة الإعلامية الحديثة وذلك بإصدار تشريعات إعلامية تحاول مواكبة التطور التكنولوجي الافتراضي و الممثلة في القانون العضوي المتعلق بالإعلام في سنة 2012 و قانون النشاط السمعي البصري في سنة 2014 . The media space is experiencing day-by-day growing radical transformations due to an increased use of the Internet and the applications and facilities it offers. E- Journalism has become an integral part of the media landscape, be it locally, nationally or internationally. The distinct attributes of the electronic press characterized by its Web coverage, speed of broadcast and wide circulation of information and news has propelled this type of media to the forefront. However, this new type of media set has created organizational problems, which are difficult to regulate. Algeria is among the countries who have recently sought to create a regulatory framework for this modern information medium by issuing two legislative Acts namely the 2012 Act on journalistic practice and the 2014 Audiovisual Act
Keywords: الإعلام الالكتروني ; التشريعات الاعلامية ; العالم الافتراضي ; الممارسة الصحفية ; Electronic press ; journalistic practice ; the web ; regulatory legislation